Development of Practical Inter-Subject Competence Application by Future Teachers of Natural Science and Mathematics - Cibulskaitė, Nijolė; Kurienė, Almeda (Pedagogika, 2015)
The paper tries to analyse what impact of didactics studies and pedagogical practice has on such abilities of prospective teachers as link sciences and mathematics teaching in practice. The aim of the research is to investigate the inter-subject links applying abilities of prospective sciences and mathematics teachers and to figure out characteristics of their vocational training in the context of the development of competencies to plan subject content and control teaching process. The general opinion of surveyed students was that application of inter-subject links in educational practice is important in order to engage pupils in sciences and mathematics as well as develop their creativity. Students also thought that the best way to implement links between subjects is to use problem-oriented education method which encourages pupils to both collaborate and individually solve given tasks. The research also revealed that students feel a lack of versatile readiness for science subjects’ integration in their practical work. The connection between sciences and mathematics subjects is tight. Processing of data achieved via experiments and solutions to exercises in natural science classes give sense to mathematics and enriches its learning and teaching experience. Such situation implies that more focus should be given for sciences and mathematical education of students.